The De Intellectu Revisited - Schroeder, Frederic; Todd, Robert (Laval théologique et philosophique, 2008)
AbstractThe author of the De Intellectu is acquainted with the De Anima of Alexander of Aphrodisias and offers a Neoplatonic interpretation of that document in its consideration of the noetic doctrine at Aristotle, De Anima 3.5. That interpretation reveals that philosophical independence from a purely philological examination of Aristotelian texts which the present volume is exploring. The De Intellectu, because of its Neoplatonic character, is to be dated some two to four centuries after Alexander. There is no reference to an Aristotle of Mytilene, teacher of Alexander, as has been supposed.